Rapidly Progressing Non-Hodgkin’s Lymphoma of Thyroid Gland - Patnaik , Madhusmita; Patnaik , Gautam; Swain, Jayshree; Kanwar , Jayabhanu (AL-Kindy College Medical Journal, 2024)
Primary Non-Hodgkin’s Lymphoma (NHL) of the thyroid gland is a rare disease comprising of 2.5 - 5% of all thyroid malignancies. It has the female preponderance, found mostly in 6th or 7th decade. The most common sub type is diffuse large B cell lymphoma (DLBCL). Ultrasonography of the neck and thyroid gland along with Fine Needle Aspiration Cytology (FNAC) are essential tools for early diagnosis of this disease. The main treatment of choice is chemotherapy following this radiotherapy. The prognosis of the patients mainly depended upon the size and grade of tumor, stage of disease and patient’s age. In this study, we report a case of a 73-year-old women rapidly growing neck mass deteriorated quickly within 10 days. The thyroid gland invades and compresses the trachea led to succumb early.